Fluid Meniscus Algorithms for Dynamic Pore-Network Modeling of Immiscible Two-Phase Flow in Porous Media - Sinha, Santanu; Gjennestad, Magnus Aa.; Vassvik, Morten; Hansen, Alex (Frontiers in Physics, 2021)
We present in detail a set of algorithms for a dynamic pore-network model of immiscible two-phase flow in porous media to carry out fluid displacements in pores. The algorithms are universal for regular and irregular pore networks in two or three dimensions and can simulate both drainage displacements and steady-state flow. They execute the mixing of incoming fluids at network nodes, distribution of fluids to outgoing links and coalescence of bubbles. Implementing these algorithms in a dynamic pore-network model we reproduce some of the fundamental results of transient and steady-state two-phase flow in porous media. For drainage displacements we reproduce the different flow patterns corresponding to viscous fingering, capillary fingering and stable displacement by altering capillary number and viscosity ratio. In steady-state flow we verify non-linear rheological properties and transition to linear Darcy behavior while increasing the flow rate. Finally we verify relations between the seepage velocities of two-phase flow in porous media considering both disordered regular networks and irregular networks reconstructed from real samples.